2010
DOI: 10.1200/jco.2009.27.0793
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Polymorphisms, Tumor Expression, Body Mass Index, Prostate Cancer Risk, and Survival

Abstract: A B S T R A C T PurposeFatty acid synthase (FASN) regulates de novo lipogenesis, body weight, and tumor growth. We examined whether common germline single nucleotide polymorphisms (SNPs) in the FASN gene affect prostate cancer (PCa) risk or PCa-specific mortality and whether these effects vary by body mass index (BMI). MethodsIn a prospective nested case-control study of 1,331 white patients with PCa and 1,267 age-matched controls, we examined associations of five common SNPs within FASN (and 5 kb upstream/dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
89
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 24 publications
10
89
1
5
Order By: Relevance
“…It has been reported that SNP rs4247357 in the FASN gene is associated with the risk of uterine leiomyomata (Eggert et al, 2012). In addition, Nguyen PL et al have reported that SNP rs1127678 in the FASN gene is associated with the risk and mortality of prostate cancer (Nguyen et al, 2010). In line with these findings, we found that two SNPs (rs4246444 and rs4485435) in FASN gene were significantly associated with the risk of recurrence in NSCLC patients, while SNP rs9912300 in ACLY gene was associated with the OS of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SNP rs4247357 in the FASN gene is associated with the risk of uterine leiomyomata (Eggert et al, 2012). In addition, Nguyen PL et al have reported that SNP rs1127678 in the FASN gene is associated with the risk and mortality of prostate cancer (Nguyen et al, 2010). In line with these findings, we found that two SNPs (rs4246444 and rs4485435) in FASN gene were significantly associated with the risk of recurrence in NSCLC patients, while SNP rs9912300 in ACLY gene was associated with the OS of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also discussed the relationship between polymorphisms of DNL genes and development and prognosis of cancers (Nguyen et al, 2010;Eggert et al, 2012). However, no studies have focused on the association between polymorphisms of ACLY, ACC and FASN and NSCLC prognosis until now.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 High level of FASN has also been linked with poor prognosis and reduced disease-free survival in prostate cancer patients. 15,16 It has been reported that overexpression of FASN induces transformation of immortalized prostate epithelial cells into invasive adenocarcinomas, and transgenic mice expressing FASN in the prostate develop intraepithelial neoplasia, suggesting that FASN has an important role in the development and progression of prostate cancer. 17 Therefore, this characteristic of cancer cells promises FASN to be a potential target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…FAS gene promoter activities were 4 to 6-fold higher in adipocytes of obese rats than in those of non-obese rats. It has been reported that FAS gene expression in human adipose tissue is associated with obesity and type 2 diabetes [32]. Chakravarthy et al (2009) have reported that a low level of FAS could protect mice from diet-induced obesity [33].…”
Section: Discussionmentioning
confidence: 99%